The psychology of unbelief - Sargent, [unknown] (The University of Edinburgh, 1941)
I The Universal Phenomenon of Religion • II The Psychological Basis of Religion • III The Emotional Inhibition to the Spiritual Life • IV Adolescent Scepticism • V The Unbelief of the Uneducated • VI The Spurious Atheism of the Passive Thinker • VII The Atheism of the Aggressive Thinker. Shelley • VIII Swinburne • IX Nietzsche • X Charles Bradlaugh • XI Sigmund Freud • XII Conclusion • Bibliography